TRAVELING TO MODERNITY: PERCEPTION OF MODERNITY OF THE CENTRAL ASIAN MUSLIMS IN THE EARLY 20TH CENTURY - Dilnoza, Jamolova (International Journal of Psychosocial Rehabilitation, 2020)
Hajj pilgrimage has been always important part of the Islamic world in terms of interrelations and knowledge sharing among various cultures. Nineteenth century brought tremendous changes to the Middle East and Asia including political integration of empires and reformation movements. Central Asian Muslims experienced the technological and economic advances of nineteenth century modernity through their journeys to Mecca. The article analyses the experience of Mulla Ālim, a Turkestani intellectual who traveled to Mecca in 1909 and became the supporter of change. It argues that, experience of haj pilgrims became important ritual to increase the number of supporters in reformer intelligentsia in Turkestan. It also asserts that admiration of the Turkestani intellectuals on social and religious in Ottoman Empire impacted their activities towards contributing to reformation of social order by education.